Penerapan Lembar Kombinasi Letter Kids Berbasis Project Upaya Peningkatan Sikap Kreatif dan Keterampilan Menulis Surat Sederhana - Zelyka, Nanda Diva; Purwati, Panca Dewi (YASIN, 2025)
Personal letter writing skills and creative attitudes among primary school students remain suboptimal, as indicated by difficulties in generating ideas, organizing letter structure coherently, and selecting appropriate language, while predominantly teacher-centered instruction constrains exploration and creativity, resulting in monotonous writing products. This study aims (1) to describe the implementation of the combined Letter Kids student worksheet (Lembar Kerja Murid, LKM) based on Project-Based Learning (PJBL) in teaching personal letter writing, (2) to analyze its effectiveness in enhancing creative attitudes, and (3) to evaluate improvements in students’ writing skills. A mixed-methods approach was employed, involving Grade VI D students of SDN Gisikdrono 02 Semarang. Data were collected through observation, interviews, documentation, and pretest–posttest writing tests. The PJBL syntax followed six stages, namely formulating driving questions, project planning, scheduling, monitoring, product development, and reflection. The combined print and electronic Letter Kids worksheets were used primarily during the planning, implementation, and product development stages of personal letter writing. The findings indicate an increase in students’ creative attitudes in terms of fluency, flexibility, originality, and elaboration of ideas, as well as an improvement in writing scores from pretest to posttest, with an N-gain value of 0.62 (moderate category). The study concludes that the implementation of the combined Letter Kids LKM based on PJBL is effective in enhancing students’ creativity and personal letter writing skills, implying that this medium can be utilized as an innovative learning alternative that supports digital literacy and promotes learner autonomy.